Advances in Spatial Data Handling Geospatial Dynamics, Geosimulation and Exploratory Visualization - Timpf, Sabine; Laube, Patrick; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This volume is based on the reviewed and edited proceedings of the International Symposium on Spatial Data Handling 2012, held in Bonn. The 15th SDH brought together scholars and professionals from the international GIScience community to present the latest research achievements and to share experiences in Geospatial dynamics, geosimulation and exploratory visualization.
Modeling and Analysis of Movement Data -- Geosimulation -- Spatiotemporal Data Structures and Algorithms -- Spatiotemporal Modeling and Analysis -- Modeling Spatial Dynamics -- Spatial Process Models -- Location-Based Services -- User-Generated Conten -- Geospatial Data Integration -- Spatio-temporal Information Acquisition -- Geosensor networks -- Multi-scalar Modeling and Analysis -- Geographic Information Retrieval and Dissemination -- Geographic knowledge discovery and data mining -- Spatial Decision Support Systems -- Spatial Data Mining -- Spatial Data Quality and Uncertainty -- Visual Analytics -- Exploratory Visualization of spatiotemporal data.
Keywords: Geography; Physical geography; Computer simulation; Geographical information systems; Geography; Geographical Information Systems/Cartography.; Geophysics/Geodesy.; Simulation and Modeling